2010
DOI: 10.1007/s11430-010-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow and its coalbed gas effects in the central-south area of the Huaibei coalfield, eastern China

Abstract: Based on an analysis of the present geo-temperature field and the thermal conductivity (K) of 62 samples from the central-south area of the Huaibei coalfield in eastern China, we calculated the heat flow and plotted its distribution map. The results show that the average heat flow in the research area is about 60 mW/m 2 . It is different from other major energy basins in the North China Plate, but has close relationship with the regional geology and the deep geological setting. The heat flow is comparatively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…There is a big difference of the terrestrial heat flow between Huainan and Huaibei coalfields, while the average of Huainan coalfield is 63.7 mW·m −2 and heat flow of Huaibei coalfield is only 55.2 mW·m −2 , which is in accordance with the heat flow value (53.0 mW·m −2 ) in the Huaibei mining area by He et al (2009). However, the heat flow value is lower than the average in the south central Huaibei coalfield (60 mW·m −2 ) (Tan et al, 2010). Either the difference of regional terrestrial heat flow and the inhomogeneous distribution of heat flow, they are related with geological structure in this region.…”
Section: Structural Control Of Current Heat Flow Distributionmentioning
confidence: 81%
See 1 more Smart Citation
“…There is a big difference of the terrestrial heat flow between Huainan and Huaibei coalfields, while the average of Huainan coalfield is 63.7 mW·m −2 and heat flow of Huaibei coalfield is only 55.2 mW·m −2 , which is in accordance with the heat flow value (53.0 mW·m −2 ) in the Huaibei mining area by He et al (2009). However, the heat flow value is lower than the average in the south central Huaibei coalfield (60 mW·m −2 ) (Tan et al, 2010). Either the difference of regional terrestrial heat flow and the inhomogeneous distribution of heat flow, they are related with geological structure in this region.…”
Section: Structural Control Of Current Heat Flow Distributionmentioning
confidence: 81%
“…Although there are a vast number of research results for the Huainan-Huaibei coalfield, the analyses of coal ground temperature are mostly confined to production requirements, or geothermal characteristics of one coal mine or regional mining areas (Tan et al, 2009a(Tan et al, , 2009bLuo et al, 2011;Wang et al, 2010). While the tests of thermophysical parameters and the studies on distribution of terrestrial heat flow remain very few (Tan et al, 2010). To fill this gap, this work sampled rocks of different layers in 12 boreholes in 7 coal mines in the study area and measured thermal conductivity of 127 samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this area was also strongly impacted by the magmatic events which happened in the whole eastern China in late Jurassic and early Cretaceous. Existing research (Han, 1990;Tan et al, 2010) showed that Yanshanian magmatic rocks mainly are distributing in the north part of the Subei fault, this means the north part experienced the stronger thermal evolution than the south part due to magmatism. Therefore, the differences in the EW direction were mainly due to the tectonic movements in late Indosinian and Yanshanian.…”
Section: Discussionmentioning
confidence: 99%
“…[38]). The thermal conductivity of rock and present geothermal gradients used in the calculation of Easy R o % were measured By Tan et al [39], and the associated well-logging data and calculation process were also published in a previous work [28]. experienced stages as follows: stable in Permian; increased continuously since Early Triassic, reached the peak value (64-82 mW/m 2 ) in Middle-Late Jurassic, decreased rapidly during Cretaceous, and returned to stable in Cenozoic (Figure 4).…”
Section: The Geothermal-flow Historymentioning
confidence: 99%